Effect of Sugarcane Bagasse Bio-Compost and Manure on Carbon Fraction and N, P, K Content in Entisols and Their Relationship with Shallot Yields - Lidya Zaela Wijaya; Jauhari Syamsiyah; Suntoro Suntoro; Slamet Minardi; Rahayu Rahayu (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2025)
Bagasse, one of the largest agricultural wastes with suboptimal utilization, could improve Entisols in the tropics by enhancing soil fertility and crop productivity. This study aimed to determine the changes in humic substances and nutrient levels in Entisols and their effects on shallot yield. The study was designed using a completely randomized design, consisting of four treatments of organic matter combinations with NPK fertilizer, four single organic matter treatments, one standard NPK fertilizer dose, and one control. Each was replicated three times. The results showed that using bagasse improved soil conditions by increasing C content and nutrient levels in the soil, enhancing nutrient absorption by plants, and consequently boosting crop yields. The biochar + bagasse compost (2:4) (bio-compost) + NPK resulted in high soil organic C, humic acid, fulvic acid, nutrient availability, and plant nutrient levels, which were comparable to the manure treatment, and significantly increased shallot yield in Entisols. The findings of this study could support the development of nutrient management strategies utilizing bagasse as a potential soil amendment for Entisols.